A Preliminary Study of Catalytic Hydrothermal Conversion of Cellulose to Lactic Acid: Effects of Reaction Temperature and Metal Ion Catalyst - Shikh Mohd Shahrul Nizan Shikh Zahari; Zulastry N.A.; Azman H.H. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA